2016
DOI: 10.1111/jocn.13371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of menstrual disorders in hospital nursing staff according to shift work pattern

Abstract: Shifts with short rotation cycles and a progressive sequence do not appear to cause menstrual disorders in nurse staff who work rotating shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…In our questionnaire, the poor sleep quality was defined by suffering any of the following sleep problems: difficulty initiating sleep or insomnia (time of initiating sleep lasts more than 30 minutes), difficulty maintaining sleep, difficulty awakening or early morning awakening, dreaminess, and somnolence. As in our study, some prior studies [ 17 , 18 ] reported that there were no significant associations between dysmenorrhea and factors such as sleep-work patterns, bedtime, and sleep durations, while the association between period pain and sleep quality was significant [ 19 ]. Similarly, a Korean study reported that there was a significant association between sleep disturbance and menstrual problems ( P = 0.003) in Korean girls aged 12~18 years old [ 14 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In our questionnaire, the poor sleep quality was defined by suffering any of the following sleep problems: difficulty initiating sleep or insomnia (time of initiating sleep lasts more than 30 minutes), difficulty maintaining sleep, difficulty awakening or early morning awakening, dreaminess, and somnolence. As in our study, some prior studies [ 17 , 18 ] reported that there were no significant associations between dysmenorrhea and factors such as sleep-work patterns, bedtime, and sleep durations, while the association between period pain and sleep quality was significant [ 19 ]. Similarly, a Korean study reported that there was a significant association between sleep disturbance and menstrual problems ( P = 0.003) in Korean girls aged 12~18 years old [ 14 ].…”
Section: Discussionsupporting
confidence: 66%
“…More studies were needed to establish a questionnaire scale to evaluate the menstrual health of females. Moreover, epidemiologic studies on the converse relationship between sleep disturbance and menstrual cycle irregularity are limited [ 17 ]. Biological and genetic mechanisms between women's sleeping status and menstrual problems need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of rotating shifts on dysmenorrhea is still controversial. While the study on 113 women working rotating shift and 75 women working day shift reported that rotating shift was not associated with dysmenorrhea, 15 a study on 420 Taiwanese nurses showed that a higher percentage of women with dysmenorrhea worked under three shift rotations than women without dysmenorrhea (91.3% vs 82.9%, P = .014) 14 …”
Section: Introductionmentioning
confidence: 96%
“…No increased risk of having menstrual disorders was reported among nurses on the rotating shift in another observational study that included 113 workers on the rotating night shift and 75 on the day shift. 13 It was found that the irregular menstruation rate was higher among the nurses. 4 A national-based study in China reported that the ratio of female nurses who experienced menstrual disorders (41%) was significantly higher than those of non-nurse health care workers.…”
Section: Minimum-maximum Mean±sdmentioning
confidence: 98%